2007
DOI: 10.1111/j.1445-2197.2007.04085.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Compression in the Prophylaxis of Venous Thromboembolism

Abstract: Venous thromboembolism (VTE) is an important cause of morbidity and mortality in a substantial number of the Australian community. There exists a considerable range of potential prophylactic measures aimed at reducing the risk of VTE. These antithrombotic regimens include pharmacological interventions and mechanical techniques to counteract venous stasis including graduated compression stockings and intermittent pneumatic compression (IPC) devices. This review particularly concentrates on evidence for the use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 67 publications
0
31
0
Order By: Relevance
“…To prevent thrombus extension, decrease of the risk of recurrent thrombosis and subsequent death in patient with VTE pharmacological and/or mechanical approaches can be administered [8, 32, 33]. …”
Section: Prevention and Treatmentmentioning
confidence: 99%
“…To prevent thrombus extension, decrease of the risk of recurrent thrombosis and subsequent death in patient with VTE pharmacological and/or mechanical approaches can be administered [8, 32, 33]. …”
Section: Prevention and Treatmentmentioning
confidence: 99%
“…In addition to increasing mortality, DVT also prolongs hospitalisation which increases healthcare costs [2]. The valvular destruction associated with a dislodged thrombus leads to post-thrombotic chronic venous insufficiency in 30% of cases as well as venous ulceration and the risk of recurrent DVT [3,4]. The incidence rates of DVT remain unacceptably high with rates as high as 30% in general surgical patients and 85% in orthopaedic patients without prophylaxis [5-8].…”
Section: Introductionmentioning
confidence: 99%
“…7,10,12,13 However, other potential factors that may be involved in CVD progression have not been well studied, such as estrogen treatment (ET), 10,11,14 and warrant further investigation. On the other hand, although many studies have shown that elastic compression stockings are the keystone of CVD treatment in the context of symptom relief, 15 ulcer healing, 16 and antithrombotic prophylaxis, 17 limited evidence is present on supportive role of elastic stocking use (ESU) in the inhibition of CVD progression that is limited mainly to patients with post-thrombotic etiology. 18 Although the advents of color duplex ultrasound (CDU) imaging and improvements in the classification of CVD 19 have significantly enhanced our current understanding of the underlying pathophysiology, studies on the natural history and progression of CVD are still scarce.…”
mentioning
confidence: 99%